2019
DOI: 10.1177/2050312119827096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutritional status of pregnant women on birth weight of newborns at Butajira Referral Hospital, Butajira, Ethiopia

Abstract: Back ground:Maternal nutritional status influences the developmental environment of the fetus which consequently affects the birth weight of the newborn. However, the association between maternal nutritional factors and birth weight is complex and is not well characterized in Ethiopia.Objective:To assess the effect of maternal anthropometry and biochemical profile on birth weight of babies at Butajira Referral Hospital, Butajira, Ethiopia.Methods and materials:Laboratory-based cross-sectional study was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 27 publications
1
40
1
6
Order By: Relevance
“…A systematic review by Marvin-Dowle et al [11] reported that pregnant adolescents have low macro and micronutrient intakes when compared to the recommended dietary allowances (RDA). Many studies suggest pre-pregnancy and pregnancy anthropometrics status such as excess weight gain, low weight, low MUAC, and maternal anaemia are strongly associated with preterm birth, and low birth weight infants in pregnant adults [12][13][14][15][16][17][18]. Another study in Ghana also reported an increase in oxidative biomarkers such as c-reactive protein, and low total antioxidant capacity during pregnancy [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review by Marvin-Dowle et al [11] reported that pregnant adolescents have low macro and micronutrient intakes when compared to the recommended dietary allowances (RDA). Many studies suggest pre-pregnancy and pregnancy anthropometrics status such as excess weight gain, low weight, low MUAC, and maternal anaemia are strongly associated with preterm birth, and low birth weight infants in pregnant adults [12][13][14][15][16][17][18]. Another study in Ghana also reported an increase in oxidative biomarkers such as c-reactive protein, and low total antioxidant capacity during pregnancy [19].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the added nutrients requirements for teenage pregnant girls need for their growth, the above-reported de ciencies would have a severer consequence for pregnant teenagers. The lifelong negative consequences of poor birth outcomes make the need to address poor nutrition among adults, but more importantly teenagers even more crucial [2,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, malnutrition among pregnant women is a major risk factor for adverse birth outcomes [12]. It will increase risks of prematurity, small for gestational age, neural tube defect, intrauterine growth restriction, low birth weight and a weakened immune system [13][14][15]. Furthermore, evidences showed these children were suffered from long term consequences like insu cient cognitive development, glucose metabolism abnormality and impaired body system functions [12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fetal growth and birth weight are also influenced by maternal weight, height, body mass index (BMI) and total gestational weight gain [16][17][18][19][20]. From these anthropometric measurements, BMI during pregnancy and gestational weight gain have been identified as the most important determinants of birth weight [19,20].…”
Section: Introductionmentioning
confidence: 99%